Let's Go to Dookey Chase's - Massie, Samuel (1987)
Draft of an address given by Samuel P. Massie (1919-2005) on the occasion of receiving the Henry A. Hill Award. The Henry A. Hill Award, now known as the Dr. Henry A. Hill Distinguished Lecturer, is awarded by the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) to an "outstanding Scientist or Engineer."
Keywords: National Organization for the Professional Advancement of Black Chemists and Chemical Engineers; Massie, Samuel; Speeches; Lectures; Science--Awards; Scientists, Black; Scientists; Chemists; African American chemists; Engineers; African American engineers